2013
DOI: 10.4258/hir.2013.19.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Health Information Technology Safety: From Technology-Induced Errors to Current Approaches for Ensuring Technology Safety

Abstract: ObjectivesHealth information technology (HIT) research findings suggested that new healthcare technologies could reduce some types of medical errors while at the same time introducing classes of medical errors (i.e., technology-induced errors). Technology-induced errors have their origins in HIT, and/or HIT contribute to their occurrence. The objective of this paper is to review current trends in the published literature on HIT safety.MethodsA review and synthesis of the medical and life sciences literature fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 34 publications
0
40
0
2
Order By: Relevance
“…Borycki [ 28 ] warned that new healthcare technologies could introduce technology-induced errors, while we have not paid much attention, in terms of patient safety, to medical device alarms. There is no Korean study that can be compared with this study; however, the results of this study were differed insignificantly from those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Borycki [ 28 ] warned that new healthcare technologies could introduce technology-induced errors, while we have not paid much attention, in terms of patient safety, to medical device alarms. There is no Korean study that can be compared with this study; however, the results of this study were differed insignificantly from those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have described positive outcomes from HIT, including support for the management of chronic diseases, facilitation of communication as part of care transitions, and improvements in patient safety by providing necessary information to all providers [ 7 8 ]. There is also a wide body of research that describes numerous challenges to implementing HIT in organizations, including workflow, communication and cognitive issues, and medical errors that are mitigated by the use of HIT [ 9 10 11 12 ]. Further, studies have reported that HIT adoption has had minimal impact on the quality of care, measured by patient mortality, adverse drug events, and readmission rates [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, despite the implementation issues, governments continue to spend large amounts of money on the adoption of HIT [ 14 ]. Organizational and social issues (OSIs) contribute to HIT implementation issues [ 10 11 15 16 ]. While some studies have explicitly studied or discussed OSIs in HIT [ 15 16 17 18 19 ], much of the research on OSIs has been imbedded in studies of post-implementation issues, such as unintended consequences and adverse events [ 9 10 11 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another result that draws attention refers to the discrepancy between the infused dose of noradrenaline identified by Nurse 5 and the prescribed one, which may have been caused, among other reasons, by the design of the infusion pump. The role of equipment design has interested researchers that work on the perspective of patient safety because of the risk of adverse events it may present (22)(23) . In accordance with the situation described during the handling of the infusion pump, studies stress types of errors in which design is a contributing factor, such as the investigation that reports the circumstance of use of defibrillators for cardiopulmonary resuscitation (22,24) .…”
Section: Discussionmentioning
confidence: 99%